Microalgal and cyanobacterial extracts in the tissue cultures of higher plants (pea, tobacco, beet) - Molnár, Zoltán; Ördög, Vince (Acta Biologica Szegediensis, 2005)
The empirical approach that has been extensively used in studies on ABSTRACT in vitro organogenesis has shown that success is largely dependent on three factors: explant choice, medium composition, and control of the physical environment. Manipulation of these factors leads to the initiation of organized development. It is well known that the concentration and combination of growth regulators govern plant regeneration. There is accumulating evidence that some of the hormones which operate in higher plants could have similar roles in algae, even in microalgae and cyanobacteria. The in vitro culture of recalcitrant plants (such as pea, beet) needs other organic growth substances than plant hormones. In this study we have evaluated the beneficial effects of some extracellular compounds derived from axenic cultures of microalgae. The dilution of freeze-dried biomass from some microalgae and cyanobacteria could be useful for the improvement of in vitro culture media of economically important crops.